Explanation of factors forming missed nursing care during the COVID-19 pandemic: A qualitative study - Safdari, Ali; Rassouli, Maryam; Elahikhah, Maryam; Ashrafizadeh, Hadis; Barasteh, Salman; Jafarizadeh, Raana; Khademi, Fatemeh (Frontiers in Public Health, 2023)
Background: Providing nursing care to patients with COVID-19 has put additional pressure on nurses, making it challenging to meet several care requirements. This situation has caused parts of nursing care to be missed, potentially reducing the quality of nursing care and threatening patient safety. Therefore, the present study aimed an explanation of factors forming Missed Nursing Care during COVID-19 Pandemic from the perspective of nurses. Methods: This qualitative study was conducted by a conventional content analysis approach in Iran, 2020-2021. Data were collected through in-depth, semi-structured interviews with 14 nurses based on purposive sampling. Data analysis was performed simultaneously with data collection. Graneheim and Lundman's approach was used for data analysis, and MAXQDA software was used for data management. After transcribing the recorded interviews, in order to achieve the accuracy and validity of the study, the criteria proposed by Lincoln and Guba were considered and used. Results: A total of 14 nurses with mean age and standard deviation 31.85±4.95 working in the COVID-19 wards participated in the study. The acquired data were put in 4 main categories including "Care-related factors," "Disease-related factors," "Patient-related factors," and "Organization-related factors," and 14 subcategories. Conclusion: The results of this study showed that several reasons including factors related to care, patient, disease and organization cause Missed Nursing Care. By modifying the related affecting factors and considering the effective mechanisms to minimize the missed nursing care, it is possible to provide better services.